2021
DOI: 10.3390/molecules27010169
|View full text |Cite
|
Sign up to set email alerts
|

Water Extract of Fritillariae thunbergii Bulbus Inhibits RANKL-Mediated Osteoclastogenesis and Ovariectomy-Induced Trabecular Bone Loss

Abstract: Fritillariae thunbergii bulbus has been widely used to treat symptoms of coughs and airway congestion in the chest due to pathological colds and damp phlegm in traditional Chinese medicine. Despite its long history of traditional use, its pharmacological activities on osteoclastogenesis and osteoporosis have not been evaluated. This study investigated the effects of the water extract of Fritillariae thunbergii bulbus (WEFT) on osteoclast differentiation in bone marrow-derived macrophage cells and on ovariectom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In this study, UPLC-tandem mass spectrometry analysis was utilized to characterize the components of FTB. Using retention time (Rt) and mass spectral data from reference standards and reported studies, eight alkaloids (yibeissine, peiminoside, sipeimine glucoside, sipeimine, peimisine, peimine, peiminine, and solanidine) and xanthurenic acid, which are basic components of FTB, were identified in FTB ( Table 1 and Supplementary Figure S1 ) [ 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, UPLC-tandem mass spectrometry analysis was utilized to characterize the components of FTB. Using retention time (Rt) and mass spectral data from reference standards and reported studies, eight alkaloids (yibeissine, peiminoside, sipeimine glucoside, sipeimine, peimisine, peimine, peiminine, and solanidine) and xanthurenic acid, which are basic components of FTB, were identified in FTB ( Table 1 and Supplementary Figure S1 ) [ 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…To analyze the FTB, a Dionex UltiMate 3000 UPLC system equipped with a Thermo Q-Exactive mass spectrometer was used. Chromatographic separation was performed using an Acquity BEH C18 column (100 × 2.1 mm, 1.7 µm) and the gradient setting was performed as described by Shim et al, using 0.1% formic acid in water and acetonitrile [ 21 ]. The identification of phytochemicals in FTB was performed by comparing their retention time (Rt) and mass spectral data with reference standards or based on a previous report [ 21 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Bone marrow cells (BMCs) were isolated from the femora and tibiae of 8-week-old C57BL/6J mice following the previously described method [54]. The BMCs were cultured in α-minimal essential medium (α-MEM; HyClone, Logan, UT, USA) supplemented with 10% heat-inactivated fetal bovine serum (FBS; Thermo Fisher Scientific, Waltham, MA, USA) and 20 ng/mL of M-CSF.…”
Section: Bmm Isolation and Cell Viability Assaymentioning
confidence: 99%
“…Pm also played an important role in suppressing the differentiation and function of osteoclasts and alleviating osteolysis and bone resorption (Zhu et al, 2021). Further study revealed that water extract of Fritillariae thunbergii Bulbus Inhibits RANKL‐Mediated osteoclastogenesis and ovariectomy‐induced trabecular bone loss (Shim et al, 2021). A recent study suggested that parathyroid hormone can treat bone loss by inhibiting adipogenesis and osteoclast function (Fan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%